2022
DOI: 10.1002/1348-9585.12341
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics, and consequences of verbal and physical violence against healthcare staff in Chinese hospitals during 2010–2020

Abstract: Objectives This study investigated the characteristics of workplace violence (WPV) against Chinese healthcare staff and their casualties after severe physical violence (PV). Methods We scrutinized medical WPV incidents reported online and analyzed information on timing, location, violence, criminal incentives, and casualties following severe PV in China from 2010 to 2020. Results WPVs were mostly committed by young and middle‐aged male family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Routine inpatient service is often performed by postgraduate students, resident trainees and further educational doctors who have less experience in interacting with patients and fewer medical skills which may increase the possibility of involvement in medical disputes ( 30 ). Staff in the emergency, obstetrics and pediatrics departments were the most vulnerable to WPV, a finding consistent with those of other studies ( 23 , 31 ). However, a specific specialization was not reported for many cases meaning that this result should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Routine inpatient service is often performed by postgraduate students, resident trainees and further educational doctors who have less experience in interacting with patients and fewer medical skills which may increase the possibility of involvement in medical disputes ( 30 ). Staff in the emergency, obstetrics and pediatrics departments were the most vulnerable to WPV, a finding consistent with those of other studies ( 23 , 31 ). However, a specific specialization was not reported for many cases meaning that this result should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 91%
“…Perpetrators were often relatives of patients rather than patients themselves, a phenomenon that has been reported across different time periods, including the COVID-19 pandemic, and different cultures ( 2 , 33 ). Family members may suffer psychological stress and have to deal with complicated medical procedures, expenses and other issues, generating more quarrels ( 31 ). Perpetrators were found to be generally poorly educated and many were farmers or unemployed, consistent with previous studies ( 7 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is in parallel with the data in crowded countries such as India and China. [9][10][11] If we look at the type of violence, we observed that verbal violence was significantly higher in our study in parallel with other studies. [6] When compared before and after the pandemic, it was observed that physical violence decreased significantly more.…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, studies have identified a higher prevalence of VV than PV among medical staff (32,33). Another study also supported that nurses were at higher risk of PV and doctors were at higher risk of VV (34). In Turkey, one study supported that average working time per week was associated with PV but not with VV among nurses (35).…”
Section: Discussionmentioning
confidence: 93%